Comparative analysis of risk factors associated with degeneration of adjacent segments: zero-profile anchored spacer vs. anterior cervical plate and cage construct - Wu, Zhikai; Wang, Wenhao; Zhou, Feng; Xiang, Pan; Li, Yangfeng; Yang, Huilin; Chu, Genglei (Frontiers in Medicine, 2024)
Objective: Anterior cervical discectomy and fusion (ACDF) is an established treatment for cervical degenerative disc disease, but cervical spine surgery may affect sagittal alignment parameters and induce the adjacent segment degeneration (ASD). The aim of this study was to determine the risk factors for developing ASD following anterior cervical plate and cage (ACPC) compared with the use of zero-profile anchored spacer (ROI-C). Methods: A retrospective contrastive study include 105 patients who underwent ACPC or ROI-C between January 2014 to October 2019, at our treatment center. There were 50 cases in the ROI-C group and 55 patients in ACPC group. Clinical and radiological results and the incidence of ASD were assessed after surgery. All patients were further divided into the ASD and non-ASD group for subgroup analysis. Results: At each follow-up time, there was no statistically significant in radiographic parameters between the two groups. The overall ASD rate was higher in ACPC group than in the ROI-C group (65.5% vs. 44.0%, P=0.027). The low preoperative Cobb angle, low preoperative segment angle (SA), and loss of Cobb (ΔCobb) were significantly correlated with ASD. However, clinical outcomes were not associated with ASD at any post-operative follow-up visit. Conclusions: Equally good therapeutic effects were achieved with both the ROI-C and ACPC. The occurrence of ASD was considerably higher in the ACPC group than in ROI-C group. The preoperative Cobb angle, preoperative SA, and ΔCobb were the most associated with an increase in the risk of ASD.